PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE MAKE A MATCH BERBANTUAN MEDIA QUESTION CARD UNTUK MENINGKATKAN MINAT BELAJAR SISWA KELAS XI SMA NEGERI 1 BINTAN UTARA - Azzahra, Mauren; Isjoni; Asril (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aimed to improve the learning interest of Grade XI students at SMA Negeri 1 Bintan Utara through the implementation of the Make a Match cooperative learning model assisted by Question Card media in History learning. This research employed Classroom Action Research (CAR) using the Kemmis and McTaggart model, conducted in two cycles consisting of planning, action, observation, and reflection stages. The research subjects were Grade XI students of SMA Negeri 1 Bintan Utara. Data were collected through observations of teacher and student activities and student learning interest questionnaires. The results showed that teacher activity increased from 75% in Cycle I to 90% in Cycle II, student activity increased from 78% to 92%, and students’ learning interest significantly improved, as indicated by an increase in the average percentage of learning interest from 74% in Cycle I to 86% in Cycle II, exceeding the predetermined success indicators. Therefore, the Make a Match cooperative learning model assisted by Question Card media was proven to be effective in increasing students’ learning interest in History learning.